Revisiting the Origin of Species : The Other Darwins - Hoquet, Thierry; Taylor and Francis (Boca Raton, FL : Routledge, an imprint of Taylor and Francis, 2018)
Contemporary interest in Darwin rises from a general ideal of what Darwin s books ought to contain: a theory of transformation of species by natural selection. However, a reader opening Darwin s masterpiece, On the Origin of Species, today may be struck by the fact that this "selectionist" view does not deliver the key to many aspects of the book. Without contesting the importance of natural selection to Darwinism, much less supposing that a fully-formed "Darwinism" stepped out of Darwin s head in 1859, this innovative volume aims to return to the text of the Origin itself. Revisiting the 'Origin of Species' focuses on Darwin as theorising on the origin of variations; showing that Darwin himself was never a pan-selectionist (in contrast to some of his followers) but was concerned with "other means of modification" (which makes him an evolutionary pluralist) Furthermore, in contrast to common textbook presentations of "Darwinism", Hoquet stresses the fact that On the Origin of Species can lend itself to several contradictory interpretations. Thus, this volume identifies where rival interpretations have taken root; to unearth the ambiguities readers of Darwin have latched onto as they have produced a myriad of Darwinian legacies, each more or less faithful enough to the originator s thought. Emphasising the historical features, complexities and intricacies of Darwin s argument, Revisiting the 'Origin of Species' can be used by any lay readers opening Darwin s On the Origin of Species. This volume will also appeal to students and researchers interested in areas such as Evolution, Natural Selection, Scientific Translations and Origins of Life.
Introduction. The meanings of "Darwinism" --Part I. Darwin-the-Selectionist and beyond -- Chapter 1. A labyrinthine Origin -- Chapter 2. Diffracting Darwins title The prism of translations -- Chapter 3. "One long argument"? Darwin-the-Selectionist --Part II. Darwin-the-Variationist -- Chapter 4. Darwin-the-Epicurean. Chance and laws of variation. -- Chapter 5. Darwin-the-Teleologist. Are all variations useful? -- Chapter 6. Darwin-the-Lamarckian and the Other "Means of Modification" --Part III. Radical origins: Darwin-the-Cosmologist -- Chapter 7. "Mystery of mysteries": the temptation of origin -- Chapter 8. "Originally Breathed": or, on the Origin of Life -- Chapter 9. "Light will be thrown": or, on the Origin of Mankind -- Chapter 10. Darwin-the-Darwinist, Or the Quest for Systematic Coherency --Conclusion. Darwinisms, or Darwin Diffracted.
Includes bibliographical references and index.
Also available in print format.
Keywords: SOCIAL SCIENCE / Sociology / General; Evolution (Biology); Electronic books